TORC1 regulates actin dynamics to control proteasome homeostasis. Issue 7 (8th June 2022) - Williams, Thomas; Rousseau, Adrien
Abstract : The conserved protein kinase complex TORC1 is a central regulator of protein homeostasis. TORC1 is active under nutrient replete, unstressed conditions and promotes bulk protein synthesis, cell growth, and proliferation. Many stresses inactivate TORC1, including nutrient starvation. When TORC1 is inactivated, bulk protein synthesis is inhibited, and stress-responsive protein synthesis activated. Degradation of damaged or unwanted proteins is increased through autophagy activation and enhanced proteasome assembly. The 26S proteasome is composed of the 20S core particle (CP), capped with one or two 19S regulatory particles (RP). Following TORC1 inhibition, the Mpk1 kinase is activated. Mpk1 facilitates increased translation of proteasome regulatory particle assembly chaperones (RPACs), leading to increased proteasome assembly. The mechanisms underlying the RPAC translation increase remain unclear, however. Here, we show that actin depolarisation upon TORC1 inhibition causes RPAC mRNAs to associate more with actin patch structures. Increasing this interaction enhances translation further. We identified Ede1 as a protein which binds translating RPAC mRNA and show that Ede1 is required to increase RPAC mRNA association with actin patches, RPAC translation and proteasome assembly upon stress.